2019
DOI: 10.1007/s12178-019-09548-4
|View full text |Cite
|
Sign up to set email alerts
|

ACL Reconstruction with Augmentation: a Scoping Review

Abstract: Purpose of Review We reviewed the recent literature to identify and summarize new research surrounding anterior cruciate ligament reconstruction (ACLR) with augmentation in the form of additional soft tissue procedures or biologic augmentation. Specifically, we wanted to review the failure rates of these procedures in both the primary and revision settings. Methods The databases Embase, PubMed, and Medline were searched on August 13, 2018, for English-language studies that reported on the use of anterior cruci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…Some applications with biological agents have been used to increase treatment effectiveness. The platelet-rich plasma (PRP) is one of the main biological agents investigated for this purpose [ 6 ]. PRP is mostly used due to its effects on the stimulation and repair of musculoskeletal injuries [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some applications with biological agents have been used to increase treatment effectiveness. The platelet-rich plasma (PRP) is one of the main biological agents investigated for this purpose [ 6 ]. PRP is mostly used due to its effects on the stimulation and repair of musculoskeletal injuries [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…They promote anabolic cell stimulation, increase in the deposition of the extracellular matrix, reduction in the pro-apoptotic and anti-inflammatory joint environment. It can be easily obtained, prepared, and applied during the ACL reconstruction surgery [ 6 ]. PRP can decrease tissue regeneration time which can be very beneficial especially for elite professional athletes [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although the benefits of PRP application during ACLR have not been confirmed for many outcomes in the reconstructed ligament, the effects of PRP on pain and knee function are significant. 6 Systematic reviews examining PRP treatment for ligament and tendon injuries 14 have pointed to a positive effect in healing and pain, although this is not a universal finding. 4 Likely, this misinterpretation of previous findings resulted from the fact that PRP-related pain reduction is higher the sooner it is measured after ACLR, as confirmed by our analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Biological evidence such as osseointegration of the graft-tunnel interface and intra-articular molecular bonding indicates beneficial effects when considering graft maturation. 17 Ventura et al performed a systematic review of the current literature on the use of PRP in ACL reconstruction and found 11 articles initially demonstrating an increase in intra-articular component remodeling of the graft during the first 10 years of follow-up. 18 Among these, one study showed an improvement in the integration.…”
Section: Prp For Acl Augmentationmentioning
confidence: 99%